Validating multi-sensor object tracking in Heavy-Duty Trucks with extended trailer dynamics for road traffic situations - Adu-Kyere, Akwasi; Nigussie, Ethiopia; Isoaho, Jouni; Ronkainen, Jukka; Kyytinen, Arto (Netherlands, 2025)
Multi-sensing technologies in vehicles have the potential to improve road and pedestrian safety. Freighting trucks with extended trailer face challenges in urban maneuvering due to limited visibility. In this paper, we evaluate and validate extended trailer dynamics for Heavy-Duty Trucks in road traffic situations with multi-sensor object tracking emphasizing trailer dynamics, back-end parameters, and characteristics that influence decision-making strategies. A custom in-vehicle compute unit, in combination with the onboard truck’s computer, facilitated this research.
The 15th International Conference on Ambient Systems, Networks and Technologies Networks (ANT) / The 7th International Conference on Emerging Data and Industry 4.0 (EDI40), April 23-25, 2024, Hasselt University, Belgium